To Compare Effectiveness and Safety of Teneligliptin vs Glimepiride in Patients with Type 2 Diabetes Mellitus (Academia Journal of Medicine, 2021)
Background: To determine the efficacy of Teneligliptin [DPP-4 inhibitor] vs Glimepiride [sulfonylurea] in patients with type 2 diabetes mellitus. Materials and Methods: Patients with inadequate glycemic control with maximum tolerable dose of metformin were randomly divided into 2 groups (Group A & Group B). Group A was started on Teneligliptin and Group B on Glimepiride. The patients were assessed for weight, fasting plasma glucose (FPG), post parandial glucose (PPG), HbA1c and Lipid Profile. The patients were followed up in OPD for 3 months. The difference in all the mentioned parameters were used to determine the efficacy of Teneligliptin V/S Glimepiride. Result: There were more males as compared to females. Most of the subjects in both the groups were having age >50 years. Mean age in group A and B was 58.72±12.78 and 59.31±13.06 years individually. Family history of diabetes was discovered in 38.69% and 45.61% of the subjects in group A and B individually. The duration of diabetes was 42.11% and 47.37% of the subjects in group A and B since 5-10 years. Hypertension and cardiovascular disease were found in 14.04%, 5.26% and 19.30%, 3.51% of the subjects in group A and B. Lipid profile viz. Cholesterol, HDL, LDL and VLDL was similar among both the groups as p>0.05. Conclusion: In the current research, Glimepiride as well as Teneligliptin were very much endured when added to Metformin. Patients on Metformin+Teneligliptin displayed better command in control of glycemic profile as well as lipid profile. Thus, Teneligliptin is the better choice as an add-on medication to Metformin in type 2 diabetes patients.
Keywords: Teneligliptin; Glimepiride; Type 2 Diabetes Mellitus